Optimalisasi Produksi Olahan Lemon melalui Teknologi Pengeringan Dehidrator di UMKM Andrau Nursery: Optimization of Processed Lemon Production through Dehydrator Drying Technology at MSME Andrau Nursery - Meiyanti Ratna Kumalasari; Puput Iswandyah Reysharie; Ida Bagus Suryanatha; Siti Unvaresi Misonia Beladona; Laila Zahra; Irvan Maulana Fiqih (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Lemon (Citrus limon L.) is a high-value horticultural commodity with growing demand, yet national production cannot meet domestic demand. Andrau Nursery, a Micro, Small, and Medium Enterprise (MSME) in Palangka Raya, has the potential to develop lemon-based products but faces challenges such as unstable sales of fresh fruit, spoilage due to the short shelf life, and suboptimal utilization of low-grade lemons. The proposed solution is to apply dehydrator technology to create value-added products such as dried lemon slices, powder, and herbal tea, which have a longer shelf life and a broader market. Community service activities were conducted through surveys, training, and mentoring on using the dehydrator. The results showed a significant increase in participants' understanding and skills, with 90% becoming familiar with the dehydrator and 100% stating the technology was more efficient than traditional methods. The processed products were more hygienic, higher in quality, and helped reduce lemon waste. Thus, the application of the dehydrator at Andrau Nursery MSME reduces harvest waste, expands product diversification, and strengthens the competitiveness of the local horticulture-based business.